Hubungan tingkat pengetahuan orang tua dengan pencegahan diare pada anak balita - Yessica Hotmaida Tarihoran; Selvia Yolanda Dalimunthe; Utari Ariyanti; Sarma Siahaan (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Diarrhea is a health problem in toddlers that continues to cause high morbidity and mortality. Low parental knowledge about clean and healthy living behaviors can impact diarrhea prevention efforts in toddlers. Purpose: To determine the relationship between parental knowledge and diarrhea prevention in toddlers. Method: A descriptive correlation design was used with a cross-sectional approach. The study population was all parents of toddlers, with a sample size of 48 respondents drawn using a total sampling technique. Data were collected using a questionnaire regarding knowledge levels and diarrhea prevention in toddlers. Data were analyzed using univariate and bivariate methods using the chi-square test with a 95% confidence level (α=0.05). Results: The majority of respondents (27 respondents) were aged 31–40 years, 27 (56.3%) were housewives, and 22 (45.8%) had a high school education. Respondents with low knowledge mostly reported poor diarrhea prevention practices (22 respondents) (45.8%). The chi-square test yielded a p-value of 0.024 (<0.05), indicating a significant relationship between parental knowledge and diarrhea prevention in toddlers. Conclusion: There is a relationship between parental knowledge and diarrhea prevention in toddlers. The better the parental knowledge, the better the diarrhea prevention efforts. Keywords: Diarrhea Prevention; Parental Knowledge; Toddlers.